Chin Interfaces for Peripheral Interaction - Ables, Brandon (ACM, 2024)
The chin interface is a wearable device that allows for peripheral interaction during everyday activities. Simple sensors and software use steady and unsteady movement data generated from everyday activities like eating, exercising, practicing guitar, or using the computer to interact with peripheral screens directed through the chin. One, two, and three button iterations of the chin interface require different levels of attention for distinct peripheral interaction experiences. Different experiences with peripheral screens can include playing back text one word at a time, slowly coloring in the letters of large words, or patiently typing out statements by selecting keys on an onscreen keyboard.
SIGGRAPH Labs ’24, July 27–August 01, 2024, Denver, CO, USA